Transition pathway towards agroecology in the semi-arid olive-based farming systems of Tunisia - Mannai, Amal; Alary, Veronique; Ouerghemmi, Hassen; Shiri, Zahra; Dhraief, Mohamed Zied; Oueslati-Zlaoui, Meriem; Majri, Rihab; Rudiger, Udo; Frija, Aymen; Idoudi, Zied; Souissi, Asma; Dhehibi, Boubaker; et al. (International Center for Agricultural Research in the Dry Areas, 2023)
Global population growth will require a 50% increase in food production by 2050. However, the current food system that promotes productivity and competitiveness has failed to provide nutritious food for all and contributes to environmental (gas emissions, pollution) and natural resources degradation (overexploitation). Therefore, a profound transformation towards ecological practices and techniques (biodiversity, natural processes, and recycling) can bring responses for designing and managing agricultural and food systems that are productive, resilient to climate change, ecologically and economically sustainable and socially equitable. In Tunisia, peasant and family farming represents 80% of farms and plays prominent role in social and food security. Olive based farming system prevails as one of the dominantly agricultural production systems in Tunisia and represents the main activity of more than two thirds of Tunisian farmers (390,000 out of 560,000). In the transect of El Kef-Siliana, in the semi-arid region of Tunisia, Olive plots are overwhelmingly owned by small scale producers, which comes with a set of challenges related to escalated soil degradation and extremely poor soil health, low productivity and incomes, and lack of commercial integration into effective value chains, etc. To help olive producers overcome these challenges, a co-design of sustainable agroecological intensification is required, which incorporates technological and organizational innovations at multiple scales with a focus on local value chain development. Current development policies in the region have emphasized inclusive and sustainable "value chains" as a key approach for systems transformation. However, due to the lack of strong administrative expertise in value chains, the implementation and proper use of this approach for rural development remains complicated. Based on this observation, and given the many local development bottleneck for this key production system, the aim of this work is to develop and validate a reflection on the transition feasibility to agroecology in this cropping system and generate a possible transition pathway that can be piloted and implemented in a given action site. The methodology used to build the most appropriate agroecological transition pathway is based on participatory approaches that include i) prospecting visits and focus group discussions with the main stakeholders as well as on ii) early visioning activities with national and local partners involved in this collective action-reflection processes (rural communities, research actors). The former process allows stakeholders, assisted by researchers, to select key farmer organizations (FOs) based on a set of predefined criteria. This was followed by interviews about the characterization and functioning of each FO, their main partners, and the main challenges they face. The latter approach was further developed and conducted with local communities and farmers. The objective is to reflect on the state of agriculture in a given FO in addition to its future evolution, and to identify one or more "desirable futures" for agriculture in 10 years from now (2022-2032). At the same time, a discussion was proposed to identify how this desirable future(s) does or does not align with the13 HLPE principles of agroecology. The AE transition pathway identified in semi-arid olive-based system suggests an emphasis on the valorization of the olive products and by-products (recycling and certified products) in addition to other agricultural practices which can be used to better align the production system with agroecological principles such as input reduction, synergies across system components, biodiversity, animal health, etc. The resulting impact pathway records promote diversified food patterns, improving soil health, increasing economic autonomy at farm and national level, diversifying market, and promotion of local products. A set of action research and development activities have been developed and will be implemented during 2023 and 2024 to pilot the suggested transition pathways and draw lessons and recommendations about wider agroecological transition in Tunisian olive-based tree systems.